The Effect of Performance Allowances and Work Discipline on Employee Performance in a Public Sector Organization - Dina Noviyanti; Sudirman Sudirman; Agustinus Djiu (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This study aims to examine the partial and simultaneous effects of performance allowances and work discipline on employee performance in a public sector organization. A quantitative approach was employed using multiple linear regression analysis. The sample consisted of 77 employees, including civil servants and government contract employees. The findings indicate that performance allowances have a positive and significant partial effect on employee performance. Similarly, work discipline also shows a positive and significant effect, with a more dominant contribution. Simultaneously, both variables significantly influence employee performance. These findings highlight that fair and timely performance-based allowances, along with consistent work discipline, are critical factors in improving employee productivity and effectiveness in the public sector. Therefore, organizations should optimize performance allowance policies by considering workload and performance achievements while strengthening discipline enforcement systems to ensure sustainable performance improvement.